2020
DOI: 10.1101/2020.07.20.212944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unique genomic features of crAss-like phages, the dominant component of the human gut virome

Abstract: CrAssphage is the most abundant virus identified in the human gut virome and the founding member of a large group of bacteriophages that infect bacteria of the phylum Bacteroidetes and have been discovered by metagenomics of both animal-associated and environmental habitats. By analysis of circular contigs from human gut microbiomes, we identified nearly 600 genomes of crAss-like phages. Phylogenetic analysis of conserved genes demonstrates the monophyly of crAss-like phages, which can be expected to become a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Samples with high proportion of viral DNA in them tended to consist of one or very few viral contigs suggesting successful enrichment ( Figure 2 ). The taxonomic range of recovered viral contigs was very wide and included prokaryotic viruses in the families Inoviridae , Microviridae , Siphoviridae , Podoviridae , Myoviridae , members of provisional group of crAss-like phages [proposed order Crassvirales ( Koonin and Yutin, 2020 ; Yutin et al., 2020 )] as well as different eukaryotic DNA and RNA viruses ( Figure 2 ). Viral community composition in enriched viral supernatants reflected the composition of original faecal virome pools, with exception of some samples where successful enrichment was evident.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples with high proportion of viral DNA in them tended to consist of one or very few viral contigs suggesting successful enrichment ( Figure 2 ). The taxonomic range of recovered viral contigs was very wide and included prokaryotic viruses in the families Inoviridae , Microviridae , Siphoviridae , Podoviridae , Myoviridae , members of provisional group of crAss-like phages [proposed order Crassvirales ( Koonin and Yutin, 2020 ; Yutin et al., 2020 )] as well as different eukaryotic DNA and RNA viruses ( Figure 2 ). Viral community composition in enriched viral supernatants reflected the composition of original faecal virome pools, with exception of some samples where successful enrichment was evident.…”
Section: Resultsmentioning
confidence: 99%
“…Some select examples of the identified phages include complete circular genomes of (i), a 45.3 kb Bacteroides uniformis DSM6597 phage ( Siphoviridae , Figure 3 ) previously observed in human gut metagenomes; (ii), a 46.4 kb temperate Siphoviridae phage infecting Anaerostipes hadrus APC942/1 ( Figure 3 ); (iii), a 168.6 kb E. coli phage ( Figure 3 ), 97% identical to previously isolated phage vB_EcoM-fHoEco02 [genus T4virus , family Myoviridae , ( Kiljunen et al, 2018 )]; (iv), a 40.3 kb Siphoviridae prophage spontaneously inducing from the chromosome of Subdoligranulum sp. APC924/74 [ Figure 3 ; ( Fitzgerald et al., 2018 )]; and (v), a 104.9 kb crAss-like phage ( Figure 3 ), belonging to subfamily Deltacrassvirinae , apparently using a non-standard genetic code [suppression of UAG codon is required to translate most of the genes ( Guerin et al., 2018 ; Yutin et al., 2020 )] and enriching in the presence of Prevotella stercorea DSM 18206. Another crAss-like phage replicating on Bacteroides intestinalis APC919/174 and identified as part of this study was previously reported ( Shkoporov et al., 2018a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crAss-like bacteriophages are a recently described family of dsDNA tailed bacterial viruses of the order Caudovirales that are predicted to infect bacteria of the phylum Bacteroidetes (Yutin et al, 2020). They are present in variety of host-associated, aquatic and terrestrial habitats, but are especially predominant in the human gut (Honap et al, 2020;Koonin and Yutin, 2020;Yutin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%